Determinasi Non Debt Tax Shield, Beban Pajak, dan Penghindaran Pajak terhadap Struktur Modal - Safitri, Afifah; Machdar, Nera Marinda (Madani: Jurnal Ilmiah Multidisiplin, 2025)
According to Weston and Brigham (1997), Capital Structure is the way an organization finances its assets. Which can be seen on the balance sheet, which consists of shareholders' equity, short-term debt, and short-term. Therefore, capital structure is only part of the financial structure (Yusuf, 2016). The purpose of this study is to see how Non Debt Tax Shield (NDTS), tax burden, and tax avoidance affect the company's capital structure. This study uses a descriptive method for literature studies. The data used comes from 44 journals accessed through Google Scholar. The results of the study indicate that tax burden, tax avoidance, and NDTS significantly affect capital structure